Polyimide film with high heat conductivity coefficient and preparation method thereof
By adding thermal filler and silicon sol to the polyimide film, a complex thermal conductivity network is formed, which solves the problem of low thermal conductivity of the polyimide film, and achieves efficient heat transfer and normal operation of electronic equipment.
Patent Information
- Application Number
- CN202510129409.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-25
AI Technical Summary
The polyimide film has a low thermal conductivity and cannot fully meet the rapid heat dissipation needs of electronic devices.
By adding thermal filler, silicon sol and silane coupling agent to the polyimide gel liquid, a complex three-dimensional thermal conductivity network is formed to improve thermal conductivity.
It significantly improves the thermal conductivity of the polyimide film, can efficiently transfer heat, reduce the risk of abnormal heat accumulation, and extend the service life of electronic equipment.
Smart Images

Figure BDA0005261046790000101 
Figure BDA0005261046790000141
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer technology, and more specifically, to a polyimide film with high thermal conductivity and a preparation method thereof. Background Art
[0002] Polymer materials are an important type of material. They are widely used in electronics, communications, military equipment manufacturing, aerospace and other industries due to their excellent electrical insulation properties, chemical corrosion resistance, low density and other characteristics. For the above industries, high-precision devices are developing in the direction of integration and small size, and related products often have both high integration and high power. With the promotion of 5G technology, the above characteristics make the impact of heat accumulation on product performance and service life an important factor that cannot be ignored. Studies have shown that for every 2°C increase in the temperature of electronic equipment, the reliability decreases by 10%, and an increase in temperature of 8-12°C will halve the service life, so the application of thermal conductive materials is very critical. Considering that polymers themselves are widely used in the above industries, many studies are devoted to the development of new polymers with good thermal conductivity.
[0003] Polyimide is an aromatic heterocyclic polymer compound constructed by chain segments containing imide groups. In addition to excellent electrical insulation, it also has good radiation resistance and mechanical properties. The film material prepared with polyimide as the main component is nicknamed "golden film". As the component closest to electronic components, polyimide film mainly plays the role of fixing and supporting electronic components. It has been widely used in printed circuit boards, electronic packaging, interlayer dielectrics, display panels and other products. At the same time, polyimide films are often located in the area where heat is most concentrated in electronic products.
[0004] With respect to the above-mentioned related technologies, the inventors believe that there is a serious scattering phenomenon when phonons are transmitted in the polyimide polymer chain, resulting in a low thermal conductivity of the polyimide film, which cannot fully meet the rapid heat dissipation requirements of electronic devices. Summary of the invention
[0005] In the related art, the thermal conductivity of polyimide film is low and cannot fully meet the demand for rapid heat dissipation of electronic devices. In order to improve this defect, the present application provides a polyimide film with high thermal conductivity and a preparation method thereof.
[0006] In a first aspect, the present application provides a polyimide film with high thermal conductivity, using the following technical solution:
[0007] A polyimide film with high thermal conductivity is prepared by curing a polyimide adhesive, wherein the polyimide adhesive comprises the following components in parts by weight: 45-50 parts of polyamic acid, 5.6-8.2 parts of thermal conductive filler, 40-45 parts of silica sol, 2.6-2.8 parts of silane coupling agent, and 370-380 parts of solvent; the thermal conductive filler comprises the following components in weight percentage: 25-30% of thermal conductive nanosheets, 13-15% of one-dimensional nanomaterials, and 18-26% of tetrapod-shaped zinc oxide, and the balance is supplemented to 100% by thermal conductive particle filler, wherein the thermal conductive particle filler comprises nano aluminum nitride.
[0008] By adopting the above technical scheme, the present application uses polyamic acid as the main component of polyimide glue, and adds thermal conductive filler, silica sol and silane coupling agent. The thermal conductive filler includes components of various shapes such as thermal conductive particle filler, one-dimensional nanomaterial, thermal conductive nanosheet, and four-needle zinc oxide, covering different dimensions from zero dimension to three dimension. The silicon dioxide nanoparticles in the silica sol are easy to combine with the thermal conductive filler and the silane coupling agent, so that the silane coupling agent can fully realize the surface modification of the thermal conductive filler and improve the dispersion effect of the thermal conductive filler. In the case where the thermal conductive filler can achieve a good dispersion effect, by stacking the thermal conductive fillers of different dimensions, a thermal conductive network with a complex three-dimensional structure can be formed in the polyimide film. At the same time, the silicon dioxide nanoparticles in the silica sol also have a certain filling effect, which can make the thermal conductive network structure more complete, and the thermal conductive filler itself has good thermal conductivity, so that the inherent defects of polyimide can be effectively overcome, and a polyimide film with a high thermal conductivity coefficient is obtained. In electronic products, the polyimide film of the present application can efficiently transfer heat, reduce the risk of abnormal heat accumulation while providing fixation and support, and thus help maintain the normal operation of electronic equipment.
[0009] Preferably, the thermally conductive nanosheets include silver nanosheets and mica nanosheets.
[0010] By adopting the above technical solution, both silver nanosheets and mica nanosheets can be used as two-dimensional thermal conductive materials to participate in the construction of thermal conductive network structures. Among them, the thermal conductive effect of silver nanosheets is more ideal and can effectively improve the thermal conductivity of polyimide films.
[0011] Preferably, the thermally conductive nanosheet further comprises imidized graphene, and the imidized graphene is prepared according to the following method:
[0012] Maleimide is dissolved in DMF, and graphene is added to the DMF. After ultrasonic mixing, the mixture is heated in an oil bath and then irradiated with ultraviolet light. After the product is cooled to room temperature, it is filtered, vacuum filtered and washed to obtain imide graphene.
[0013] By adopting the above technical solution, the present application grafts maleimide onto the graphene surface through the Diels-Alder reaction to obtain imidized graphene. The "-NH-" group of imidized graphene can react with the carboxyl group at the end of polyamic acid during the curing process of polyimide glue, and after imidization, a "CNC" covalent bond is formed, which can effectively reduce the interfacial thermal resistance between polyimide and thermal conductive filler, and help to fully improve the thermal conductivity of polyimide film.
[0014] Preferably, the polyamic acid is prepared according to the following method:
[0015] (1) Under nitrogen protection, dissolving a diamine monomer and a dianhydride monomer in DMF respectively to obtain a diamine solution and a dianhydride solution for standby use; in this step, the diamine monomer is 4,4-diaminodiphenyl ether;
[0016] (2) The dianhydride solution and the diamine solution are mixed and reacted in an ice-water bath to obtain polyamic acid.
[0017] By adopting the above technical scheme, the present application first prepares a diamine solution and a dianhydride solution respectively, and then controls the reaction of the dianhydride solution and the diamine solution to obtain polyamic acid.
[0018] Preferably, the diamine monomer further comprises 4,4-diaminodiphenylmethane.
[0019] By adopting the above technical solution, 4,4-diaminodiphenylmethane can enhance the hydrogen bonding effect in the polyimide film, limit the folding of the chain segments where 4,4-diaminodiphenyl ether is located, improve the overall orientation of the polyimide molecular chain, facilitate heat transfer, and improve the thermal conductivity of the polyimide film.
[0020] Preferably, the amount of 4,4-diaminodiphenylmethane used accounts for 45-60% of the total weight of the diamine monomers.
[0021] By adopting the above technical solution, the present application optimizes the usage ratio of 4,4-diaminodiphenylmethane, which helps to improve the thermal conductivity of the polyimide film.
[0022] Preferably, the one-dimensional nanomaterial comprises polyaniline nanotubes.
[0023] By adopting the above technical solution, polyaniline has good thermal conductivity, and polyaniline nanotubes have a one-dimensional structure, which can realize heat transfer in one-dimensional direction. In addition, the "-NH-" group on the surface of polyaniline nanotubes can also undergo a cross-linking reaction with the terminal carboxyl group of polyamic acid, forming a "CNC" covalent bond after imidization, which can effectively reduce the interfacial thermal resistance between polyimide and thermal conductive filler, and help to fully improve the thermal conductivity of polyimide film.
[0024] Preferably, the one-dimensional nanomaterial further comprises amino-modified carbon nanotubes, and the amino-modified carbon nanotubes are prepared according to the following method:
[0025] MWCNTs and MDA were added into a reaction vessel, and reacted at 200-210°C for 8-16 hours under nitrogen protection. The powder obtained after the reaction was washed with DMF and deionized water in turn to remove unreacted MDA. The obtained solid was dried in vacuum to obtain amino-modified carbon nanotubes.
[0026] By adopting the above technical solution, the present application uses MDA as a modifier, and grafts maleic acid diamine to the surface of MWCNTs through the Diels-Alder reaction to obtain amino-modified carbon nanotubes. The amino-modified carbon nanotubes themselves have good thermal conductivity, and can also undergo a cross-linking reaction with the terminal carboxyl group of polyamic acid to form a "CNC" covalent bond after imidization, which can effectively reduce the interfacial thermal resistance between polyimide and thermal conductive filler, and help to fully improve the thermal conductivity of the polyimide film.
[0027] Preferably, the weight ratio of the amino-modified carbon nanotubes to the polyaniline nanotubes is 1:(1.7-2.4).
[0028] By adopting the above technical solution, the present application optimizes the weight ratio of amino-modified carbon nanotubes to polyaniline nanotubes, which helps to fully improve the thermal conductivity of the polyimide film.
[0029] In a second aspect, the present application provides a method for preparing a polyimide film with high thermal conductivity, using the following technical solution.
[0030] A method for preparing a polyimide film with high thermal conductivity comprises the following steps:
[0031] (1) mixing polyamic acid, thermal conductive filler, silica sol, silane coupling agent and solvent to obtain polyimide glue solution for standby use;
[0032] (2) The polyimide adhesive is subjected to casting processing and biaxial stretching to obtain a polyimide film with a high glass transition temperature.
[0033] By adopting the above technical solution, the present application first prepares the polyimide adhesive, then solidifies the polyimide adhesive by casting, and obtains a polyimide film with a high glass transition temperature after biaxial stretching.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. This application improves the dispersion effect of thermal conductive fillers through the synergistic effect of silane coupling agent and silica sol. By stacking thermal conductive fillers of different dimensions, a three-dimensional thermal conductive network with a relatively complex structure can be formed in the polyimide film, and the silica nanoparticles in the silica sol are used for filling, so that the thermal conductive network structure is more complete, and finally a polyimide film with a high thermal conductivity coefficient is obtained. In electronic products, the polyimide film of this application can efficiently transfer heat, and while fixing and supporting, the risk of abnormal heat accumulation is reduced, thereby helping to maintain the normal operation of electronic equipment.
[0036] 2. This application grafts maleimide onto the surface of graphene through Diels-Alder reaction to obtain imidized graphene, grafts maleic acid diamine onto the surface of MWCNTs to obtain amino-modified carbon nanotubes, and also selects polyaniline nanotubes. The "-NH-" groups of these thermally conductive fillers can react with the carboxyl groups at the ends of polyamic acid during the curing process of the polyimide glue, and form "CNC" covalent bonds after imidization, which can effectively reduce the interfacial thermal resistance between polyimide and thermally conductive fillers, and help to fully improve the thermal conductivity of polyimide film.
[0037] 3. The present application introduces 4,4-diaminodiphenylmethane into polyamic acid. 4,4-diaminodiphenylmethane can enhance the hydrogen bonding effect in the polyimide film, limit the folding of the chain segments where 4,4-diaminodiphenyl ether is located, improve the overall orientation of the polyimide molecular chain, facilitate heat transfer, and improve the thermal conductivity of the polyimide film. DETAILED DESCRIPTION
[0038] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0039] Preparation example of imide graphene
[0040] The following is an explanation using Preparation Example 1.
[0041] Preparation Example 1
[0042] In this preparation example, imide graphene was prepared according to the following method:
[0043] 45 g of maleimide was dissolved in 40 L of DMF, and 10 g of graphene was added to the DMF. After ultrasonic mixing for 50 min, it was heated in an oil bath at 120 ° C for 16 h, and then irradiated with ultraviolet light at an intensity of 30 mW / cm2 for 13 min. After the product was cooled to room temperature, it was filtered using a polytetrafluoroethylene membrane with a pore size of 0.1 μm, and then vacuum filtered and washed with ethanol. After drying, imide graphene was obtained.
[0044] Preparation Example of Polyamic Acid
[0045] The following is an explanation using Preparation Example 2.
[0046] Preparation Example 2
[0047] In this preparation example, the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.15, the dianhydride monomer is pyromellitic anhydride, and the diamine monomer is 4,4-diaminodiphenyl ether.
[0048] In this preparation example, polyamic acid was prepared according to the following method:
[0049] (1) Under nitrogen protection, dissolving the diamine monomer and the dianhydride monomer in DMF at 20° C. to obtain a diamine solution and a dianhydride solution, respectively, for later use;
[0050] (2) The dianhydride solution and the diamine solution were mixed and reacted in an ice-water bath at 0° C. to obtain a polyamic acid with a solid content of 15% after 5 hours.
[0051] Preparation Example 3
[0052] The difference between this preparation example and preparation example 2 is that the diamine monomer further includes 4,4-diaminodiphenylmethane, and the amount of 4,4-diaminodiphenylmethane accounts for 30% of the total weight of the diamine monomer.
[0053] Preparation Example 4
[0054] The difference between this preparation example and preparation example 3 is that the amount of 4,4-diaminodiphenylmethane used accounts for 45% of the total weight of the diamine monomer.
[0055] Preparation Example 5
[0056] The difference between this preparation example and preparation example 3 is that the amount of 4,4-diaminodiphenylmethane used accounts for 50% of the total weight of the diamine monomer.
[0057] Preparation Example 6
[0058] The difference between this preparation example and preparation example 3 is that the amount of 4,4-diaminodiphenylmethane used accounts for 60% of the total weight of the diamine monomer.
[0059] Preparation example of amino-modified carbon nanotubes
[0060] The following is an explanation using Preparation Example 7.
[0061] Preparation Example 7
[0062] In this preparation example, amino-modified carbon nanotubes were prepared according to the following method:
[0063] MWCNTs and MDA were added into the reaction vessel at a molar ratio of 1:10, and reacted at 210°C for 8 hours under nitrogen protection. The powder obtained after the reaction was washed with DMF and deionized water in turn to remove unreacted MDA. The obtained solid was dried in vacuum for 12 hours to obtain amino-modified carbon nanotubes.
[0064] Preparation Example 8
[0065] The difference between this preparation example and preparation example 7 is that the reaction temperature of MWCNTs and MDA is 205° C. and the reaction time is 12 h.
[0066] Preparation Example 9
[0067] The difference between this preparation example and preparation example 7 is that the temperature for the reaction of MWCNTs and MDA is 200° C. and the reaction time is 16 h.
[0068] Example
[0069] In the following examples, “average particle size” refers to the D50 particle size.
[0070] Examples 1-5
[0071] The following description is given by taking Example 1 as an example.
[0072] Example 1
[0073] In this embodiment, the thermally conductive particle filler is nano-aluminum nitride (with an average particle size of 120 nm), the polyamic acid is prepared according to the method of Preparation Example 2, the water content of the silica sol is 70%, the silane coupling agent is KH550, the solvent is DMAc, the thermally conductive nanosheets are mica nanosheets, the one-dimensional nanomaterial is polyaniline nanotubes, and the average particle size of the four-needle zinc oxide is 35 μm.
[0074] This embodiment provides a polyimide film with high thermal conductivity. The polyimide film is made by curing a polyimide glue, wherein the polyimide glue comprises the following components by weight: 45 kg of polyamic acid, 5.6 kg of thermal conductive filler, 40 kg of silica sol, 2.6 kg of silane coupling agent, and 370 kg of solvent. The thermal conductive filler comprises the following components by weight percentage: 25% of thermal conductive nanosheets, 13% of one-dimensional nanomaterials, and 18% of tetrapod-shaped zinc oxide, and the remainder is supplemented to 100% by thermal conductive particle fillers.
[0075] This embodiment provides a method for preparing a polyimide film with high thermal conductivity, comprising the following steps:
[0076] (1) mixing polyamic acid, thermal conductive filler, silica sol, silane coupling agent and solvent to obtain polyimide glue solution for standby use;
[0077] (2) The polyimide adhesive solution is subjected to a casting process. Specifically, the polyimide adhesive solution is coated on a glass plate by a casting method, placed in an oven for temperature rise and curing, and then biaxially stretched to obtain a polyimide film with a high glass transition temperature. The film thickness is 70 μm.
[0078] In the above-mentioned casting operation, the temperature rising program in the oven is: heat to 150 ℃ in 1 hour, keep warm for 1 hour, heat to 175 ℃ in 0.5 hour, keep warm for 1 hour, heat to 200 ℃ in 0.5 hour, keep warm for 1 hour, heat to 250 ℃ in 0.5 hour, keep warm for 1 hour, heat to 300 ℃ in 0.5 hour, keep warm for 1 hour, and then wait for natural cooling to 25 ℃.
[0079] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the polyimide glue and the thermal conductive filler.
[0080] Table 1 Raw material ratio of polyimide glue and thermal conductive filler
[0081]
[0082] Example 6
[0083] The difference between this embodiment and embodiment 5 is that the thermally conductive nanosheets are silver nanosheets.
[0084] Example 7
[0085] The difference between this embodiment and embodiment 6 is that the thermally conductive nanosheet further includes imidized graphene, the imidized graphene is prepared according to the method of preparation example 1, and the amount of imidized graphene accounts for 20% of the total weight of the thermally conductive nanosheet.
[0086] Embodiment 7-11
[0087] As shown in Table 2, the difference between Examples 7-11 is that the preparation examples of polyamic acid are different.
[0088] Table 2 Preparation example of polyamic acid
[0089] sample Preparation Example Example 7 Preparation Example 2 Example 8 Preparation Example 3 Example 9 Preparation Example 4 Example 10 Preparation Example 5 Embodiment 11 Preparation Example 6
[0090] Example 12
[0091] The difference between this embodiment and embodiment 11 is that the one-dimensional nanomaterial further includes amino-modified carbon nanotubes, and the amino-modified carbon nanotubes are prepared according to the method of preparation example 7, and the weight ratio of amino-modified carbon nanotubes to polyaniline nanotubes is 1:3.
[0092] Embodiment 13
[0093] The difference between this embodiment and embodiment 12 is that the amino-modified carbon nanotubes are prepared according to the method of preparation example 8.
[0094] Embodiment 14
[0095] The difference between this embodiment and embodiment 12 is that the amino-modified carbon nanotubes are prepared according to the method of preparation example 9.
[0096] Embodiment 15
[0097] The difference between this embodiment and embodiment 14 is that the weight ratio of amino-modified carbon nanotubes to polyaniline nanotubes is 1:2.4.
[0098] Example 16
[0099] The difference between this embodiment and embodiment 14 is that the weight ratio of amino-modified carbon nanotubes to polyaniline nanotubes is 1:2.1.
[0100] Embodiment 17
[0101] The difference between this embodiment and embodiment 14 is that the weight ratio of amino-modified carbon nanotubes to polyaniline nanotubes is 1:1.7.
[0102] Comparative Example
[0103] Comparative Example 1
[0104] A thermally conductive polyimide film is prepared by the following preparation method:
[0105] (1) Add 4,4'-diaminodiphenyl ether and N,N-dimethylformamide into a dissolving kettle, stir evenly for 20 minutes at 30°C to completely dissolve 4,4'-diaminodiphenyl ether; add pyromellitic anhydride and N,N-dimethylformamide into a dissolving kettle, stir evenly for 20 minutes at 40°C to completely dissolve pyromellitic anhydride;
[0106] (2) mixing the 4,4'-diaminodiphenyl ether solution and the pyromellitic dianhydride solution in a molar ratio of diamine:dianhydride = 1:1.2, and continuing to stir uniformly at 40° C. for 4 hours to obtain a polyamic acid glue;
[0107] (3) taking the polyamic acid glue prepared in step (2) and mixing it with an inorganic additive, the inorganic additive includes 18 kg of micron-sized strip-shaped boron nitride (average particle size 10 μm), 12 kg of nano-sized rod-shaped TiO2 (average particle size 70 nm) and 30 kg of PSZ (silazane resin), stirring it evenly in an environment below 25° C., filtering it by pressure to remove impurities, and obtaining 1500 kg of a mixture with a solid content of 20%, wherein the mass fraction of the inorganic additive in the solid content of the mixture is 20%;
[0108] (4) The mixture obtained in step (3) is subjected to chemical imidization (mixed with about 312 kg of isoquinoline and 46 kg of acetic anhydride at -5°C), and then cast on a steel belt through a coating die and dried. The speed of the steel belt is controlled to be 5 m / min, and the heating temperature of the upper and lower heating tubes inside the casting machine is 190°C. The mixture is then longitudinally stretched, and a polyimide film is obtained after desolventizing and curing. The polyimide film is then stretched in a transverse stretching machine to obtain a biaxially stretched polyimide film. The thickness of the polyimide film is 70 μm.
[0109] Comparative Example 2
[0110] The difference between this comparative example and Example 1 is that the components of the polyimide adhesive do not include silica sol.
[0111] Comparative Example 3
[0112] The difference between this comparative example and Example 1 is that the components of the polyimide adhesive do not include a silane coupling agent.
[0113] Comparative Example 4
[0114] The difference between this comparative example and Example 1 is that the thermally conductive filler does not include thermally conductive nanosheets.
[0115] Comparative Example 5
[0116] The difference between this comparative example and Example 1 is that the components of the thermal conductive filler do not include one-dimensional nanomaterials.
[0117] Comparative Example 6
[0118] The difference between this comparative example and Example 1 is that the thermal conductive filler does not include tetrapod-shaped zinc oxide.
[0119] Comparative Example 7
[0120] The difference between this comparative example and Example 1 is that the thermally conductive filler component does not include thermally conductive particle filler.
[0121] Performance testing methods
[0122] The thermal conductivity of the polyimide film of each embodiment and comparative example was detected by the steady-state plate method. Then, based on the thermal conductivity of comparative example 1, the ratio between the thermal conductivity measured in each embodiment and comparative example and the thermal conductivity of comparative example 1 was calculated. The ratio was recorded as the relative thermal conductivity. The results are shown in Table 3.
[0123] Table 3 Relative thermal conductivity
[0124]
[0125] It can be seen from the combination of Examples 1-5 and Comparative Example 1 and Table 3 that the thermal conductivity coefficients measured in Examples 1-5 are all higher than those in Comparative Example 1. This is because the silane coupling agent of the present application fully realizes the surface modification of the thermally conductive filler and improves the dispersion effect of the thermally conductive filler. On this basis, by stacking thermally conductive fillers of different dimensions on each other, a thermally conductive network with a relatively complex three-dimensional structure can be formed in the polyimide film. At the same time, the silicon dioxide nanoparticles in the silica sol also have a certain filling effect, which can make the thermally conductive network structure more complete. In addition, the thermally conductive filler itself has good thermal conductivity, which can effectively overcome the inherent defects of polyimide and obtain a polyimide film with a higher thermal conductivity coefficient.
[0126] It can be seen from Example 1 and Comparative Examples 2-7 and Table 3 that when any one of silica sol, silane coupling agent, thermal conductive nanosheet, one-dimensional nanomaterial, tetrapod-shaped zinc oxide, and thermal conductive particle filler is missing, the overall thermal conductivity of the polyimide film will be affected to a certain extent.
[0127] It can be seen from Example 5 and Example 6 and Table 3 that the thermal conductivity of the polyimide film can be further improved because the thermal conductivity of the silver nanosheets is more ideal.
[0128] Combining Example 6 and Example 7 with Table 3, it can be seen that the thermal conductivity of Example 7 is higher. This is because the "-NH-" group of the imidized graphene can react with the carboxyl group at the end of the polyamic acid during the curing process of the polyimide glue, forming a "CNC" covalent bond after imidization, which can effectively reduce the interfacial thermal resistance between the polyimide and the thermally conductive filler, and help to fully improve the thermal conductivity of the polyimide film.
[0129] Combining Examples 7-11 and Table 3, it can be seen that the thermal conductivity measured in Examples 8-11 is higher, because 4,4-diaminodiphenylmethane can enhance the hydrogen bonding effect in the polyimide film, limit the folding of the chain segments where 4,4-diaminodiphenyl ether is located, and improve the overall orientation of the polyimide molecular chain, which is beneficial to the transmission of heat, thereby improving the thermal conductivity of the polyimide film. Moreover, when the amount of 4,4-diaminodiphenylmethane accounts for 45-60% of the total weight of the diamine monomer, this effect is more obvious.
[0130] Combining Example 11, Examples 12-17 and Table 3, it can be seen that the thermal conductivity measured in Examples 12-17 is higher. This is because the amino-modified carbon nanotubes themselves have good thermal conductivity and can also undergo a cross-linking reaction with the terminal carboxyl groups of polyamic acid to form a "CNC" covalent bond after imidization, which can effectively reduce the interfacial thermal resistance between polyimide and thermal conductive filler, and help to fully improve the thermal conductivity of the polyimide film. Moreover, when the weight ratio of amino-modified carbon nanotubes to polyaniline nanotubes is 1: (1.7-2.4), it helps to further improve the thermal conductivity of the polyimide film.
[0131] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A polyimide film with high thermal conductivity, characterized in that: The polyimide film is made by curing polyimide glue, wherein the polyimide glue comprises the following components in parts by weight: 45-50 parts of polyamic acid, 5.6-8.2 parts of thermal conductive filler, 40-45 parts of silica sol, 2.6-2.8 parts of silane coupling agent, and 370-380 parts of solvent; the thermal conductive filler comprises the following components in weight percentage: 25-30% of thermal conductive nanosheets, 13-15% of one-dimensional nanomaterials, and 18-26% of tetrapod-shaped zinc oxide, and the balance is supplemented to 100% by thermal conductive particle filler, and the thermal conductive particle filler comprises nano aluminum nitride.
2. The polyimide film with high thermal conductivity according to claim 1, characterized in that: The thermally conductive nanosheet includes one of a silver nanosheet and a mica nanosheet.
3. The polyimide film with high thermal conductivity according to claim 2, characterized in that: The thermally conductive nanosheet further comprises imidized graphene, and the imidized graphene is prepared according to the following method: Maleimide is dissolved in DMF, and graphene is added to the DMF. After ultrasonic mixing, the mixture is heated in an oil bath and then irradiated with ultraviolet light. After the product is cooled to room temperature, it is filtered, vacuum filtered and washed to obtain imide graphene.
4. The polyimide film with high thermal conductivity according to claim 1, characterized in that: The polyamic acid is prepared according to the following method: (1) Under nitrogen protection, dissolving a diamine monomer and a dianhydride monomer in DMF respectively to obtain a diamine solution and a dianhydride solution for standby use; in this step, the diamine monomer is 4,4-diaminodiphenyl ether; (2) The dianhydride solution and the diamine solution are mixed and reacted in an ice-water bath to obtain polyamic acid.
5. The polyimide film with high thermal conductivity according to claim 4, characterized in that: The diamine monomer also includes 4,4-diaminodiphenylmethane.
6. The polyimide film with high thermal conductivity according to claim 5, characterized in that: The amount of 4,4-diaminodiphenylmethane used accounts for 45-60% of the total weight of the diamine monomer.
7. The polyimide film with high thermal conductivity according to claim 1, characterized in that: The one-dimensional nanomaterial includes polyaniline nanotubes.
8. The polyimide film with high thermal conductivity according to claim 7, characterized in that: The one-dimensional nanomaterial further comprises amino-modified carbon nanotubes, and the amino-modified carbon nanotubes are prepared according to the following method: MWCNTs and MDA were added into a reaction vessel, and reacted at 200-210°C for 8-16 hours under nitrogen protection. The powder obtained after the reaction was washed with DMF and deionized water in turn to remove unreacted MDA. The obtained solid was dried in a vacuum to obtain amino-modified carbon nanotubes.
9. The polyimide film with high thermal conductivity according to claim 8, characterized in that: The weight ratio of the amino-modified carbon nanotubes to the polyaniline nanotubes is 1:(1.7-2.4).
10. The method for preparing a polyimide film with high thermal conductivity according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing polyamic acid, thermal conductive filler, silica sol, silane coupling agent and solvent to obtain polyimide glue solution for standby use; (2) The polyimide adhesive is subjected to casting processing and biaxial stretching to obtain a polyimide film with a high glass transition temperature.
Citation Information
Patent Citations
Low-temperature-resistant polymer insulating heat-conducting composite material and processing technology thereof
CN112251000A
High-thermal-conductivity composite particle / polyimide film with four-needle-shaped structure and preparation method of high-thermal-conductivity composite particle / polyimide film
CN112812341A
Sandwich-structure high-thermal-conductivity composite film thermal interface material and preparation method thereof
CN114516207A
Polyimide heating body and preparation method thereof
CN115434160A